Psychosocial risk and job satisfaction in professional drivers - Hernández-Rodríguez, Víctor; Maeso-González, Elvira; Gutiérrez-Bedmar, Mario; García-Rodríguez, Antonio (Frontiers in Psychology, 2022)
Psychosocial work factors are implicated in the development of stress and job satisfaction. This relationship has been scarcely studied in so-called singular activities, as is the case of professional drivers. This cross-sectional study of 601 professional drivers assesses psychosocial risks and job satisfaction using COPSOQ (Copenhagen Psychosocial Questionnaire) and Overall Job Satisfaction questionnaire models. The values of the psychosocial scales of professional drivers were compared with thresholds values of the Spanish working population. The relationships of the psychosocial scales with the level of job satisfaction were examined using logistic regression models, adjusted for age, gender, length of driving license and years of experience. In general, professional drivers have an unfavorable psychosocial environment compared to the average Spanish workers. The relationship between psychosocial scales and job satisfaction is observed, with the most influential variables being the meaning and development of work, integration in the company, social relations, esteem and level of psychological demands.